Existence of generalized, positive and periodic solutions for some differential equations of order II - Ligęza, Jan (Annales Mathematicae Silesianae, 2014)
We study the existence of positive periodic solutions of the equations y''(x) - P'(x)y(x) + μQ'(x)f(x,y(x)) = 0, y''(x) + P'(x)y(x) = μQ'(x)f(x,y(x)), where μ>0, P and Q are real nondecreasing functions, P' and Q' are 1-periodic distributions, f is a continuous function and 1-periodic in the first variable. The Krasnosielski fixed point theorem on cone is used.